ON THE ISSUE OF THE MAIN TYPES OF GRAMMATICAL AND STYLISTIC MISTAKES IN WRITTEN WORKS OF STUDENTS - Zulfiya Ruzmetova; Galina Artykova; Olga Palvanova (Web of Journals Publishing, 2024)
In this article, based on the richest factual material, typical types of grammatical and stylistic mistakes in written works of students are deeply analyzed.
Keywords: classification of mistakes, representation, violation of agreement, types of mistakes.